The changes and challenges posed by the taxation of the digital economy in the international context - Jiménez Vargas, Pedro Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
A digital economy is one that focuses on the sale of goods and services through digital platforms. This has very specific characteristics with respect to the traditional economy. The taxation of profits obtained through transactions carried out on the network have been increased exponentially, at the same time that sales in digital commerce have increased, carried out by international business organizations that operate with or without a permanent establishment. These business organizations have developed general guidelines to try to tax their income in places with little or no taxation. One of the main problems that arise in e-commerce activity is to determine who is the final effective beneficiary of the income obtained.
Keywords: taxation; beneficial owner; digital economy; digital presence; Regulations